Pão sem glúten enriquecido com inulina: um estudo de otimização do novo produto e de comparação das suas propriedades físicas, aceitabilidade, vida de prateleira e resposta glicêmica com as de pães convencionais - Muniz, Denise Garcia [UNIFESP] (2016)
This study aims to define the appropriate levels of inulin and water in order to add technological, nutritional and functional quality to gluten-free breads (GFB). The central composite design was used, with variations of inulin (I) levels from 0 to 30% and water (W) of 80 140% (on flour basis - fb). Results have shown that the addition of up to 30% I does not affect the physical properties and acceptability of GFB, provided that appropriate setting of the W percentage of the formulations be accomplished. Two formulations were selected: one for the simultaneous optimization of the acceptability by the overall desirability function (D = 0.96), consisting of 10.65% I and 108.5% W (fb) and the other by the overlapping of the acceptability contour graphs, consisting of 30% I and 131.6% W (fb). These formulations, as well as the control one (without I) showed acceptability scores of appearance, color, aroma, flavor, texture and overall acceptability of ? 8 in hybrid hedonic scale of 10 cm. The use of 30% I (fb) in the preparation of GFB resulted in a well-accepted product containing 7.7% of fructan in the formulation and 10.2% total dietary fiber; corresponding to a 3.6 times increase in fiber content compared to the control formulation. The results of the in vivo test for determining the glycemic response showed that this level of addition caused a significant reduction in the glycemic index from 67 to 49, and the glycemic load from 14 to 8 GFB. Results of the shelf life test have shown that the addition of 30% I (fb) did not alter the physical properties of GFB, and these showed higher crumb firmness when compared to the two formulations of bread made of wheat flour (WB1 and WB2). The lowest acceptability scores of texture and taste were the characteristics that differentiate the GFB of WB1 and WB2 bread during the 72 hours storage. It has been observed that 24 hours after production, the GFB control is no longer accepted for texture (scores between 4 and 5) and addition of I allowed the maintenance of moderate acceptance of this attribute (~ 6 scores) during 72 hours storage. The use of 30% I and 131.6% W (fb) in GFB formulation enable to obtain a nutritionally-improved product that can provide nutritional and functional benefits to people who need gluten-free diet and / or glycemic control. Considering the high nutritional and functional potential of this product, further studies leading to extend their shelf life are recommended.